Pattern of Ocular Myasthenia Gravis in a Tertiary Eye Care Hospital, Bangladesh - Sarkar, Shayamal K; Rumki, Hasina; Rahman, Munsur; Alam, Md Toriqul; Hossain, Monir; Sultana, Zakia (Journal of National Institute of Ophthalmology, 2022)
Purpose: The purpose of this study was to evaluate pattern of ocular myasthenia gravis patients in a tertiary eye care hospital in Bangladesh. Methodology: This observational study was conducted in National Institute of Ophthalmology and Hospital (NIOH), Dhaka from January 2019 to December 2019. A total of 33 cases were purposively selected among ocular myasthenia gravis patients attending in the Department of neuro ophthalmology of NIOH irrespective of age, gender, residence. Study variables wereage, gender, clinical features, presence of thymoma, clinical, pharmacological and serological test findings. A proforma was prepared to record the data on particulars of the patients. Results: Among the cases, 45.5% were male and 54.5% were female where the mean age was 38.7 years. All patients presented with ptosis (100.0%) and most of them had fatigability(87.9%), cogan twice sign (81.8%) andorbicularis weakness (81.8%) while 63.6% had diplopia. Diabetes mellitus was observed in 18.2%patients and 15.1% had thyroid associations. Most of them had positive ice test(87.9%), 51.5% had positive serological test and 6.1% had positive neostigmine test. Thymoma was present in 6.1% cases. Conclusion: Ptosis was the most common clinical presentation for ocular myasthenia. Clinical diagnosis was confirmed by ice pack test and neostigmine test. Ocular myasthenia gravis patients may be have other systemic diseases. J. Natl. Inst. Ophthalmol. 2022;5(1):16-20